Determination of some heavy metals and microbial profile of raw Sugar samples collected from Sudanese Sugar Industries in season 2017 in relation to EU.1998 and ICUMSA,1974 standards - AM Babeker; AR Ahmed; GI Mastafa; AA Abdalla; A Bakur (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2022)
The study was conducted in Sudanese Sugar Industries during the period 2017 to aim the determination some heavy metals and microbial profiles of raw Sugar samples collected from Sudanese Sugar Industries in season 2017 in relation to EU.1998 and ICUMSA,1974 standards. The samples were obtained from all Sudanese Sugar Industries namely, (Kenana, White Nile, Assalaya, Sennar, Guneid, and New Halfa). After that the samples were transferred to the laboratory to assess the quality parameters of raw sugar which include the determination of some heavy metals content of sugar cane per mg/kg in Sudanese sugar companies which include Mercury, Cadmium, Lead, and Arsenic, Determination Microbial analysis for final sugar which includes Detection of Thermopolis Bacteria (Sporeforming Bacteria, Bacteria producing H2S and H2 swell) and Determination Methophilic Bacteria (Total Count of bacteria CFU/10 gm, Determination Coliform Bacteria CFU/ 10 gm, Determination of Leuconstoc Mesenteroides Bacteria CFU/10 gm. and Enumeration of Yeasts and Moulds CFU/ 10 gm and Determination the concentration of Dextran. and the data were analyzed by using a Statistical system Complete Randomized Design (CRD) and analysis of variance technique by Least Significant Different Test (LSD) according to Fisher's LSD method, 2010 at (Probability 0.05). Was applied to compare differences between means. The results showed that the mean concentration of Mercury, Cadmium, Lead and Arsenic was (0.02 mg/ kg grams of sugar), (0.62 mg/ kg sugar), (6.74 mg/ kg sugar), and (2.73mg/ kg sugar). These results Indicate all sample industries were agreeable with critical limit maximum value. It was concluded that the total count of Bacteria for raw Sugar White Nile and Sennar agreed with recommended limit. In the case of total yeasts, Sporeforming Bacteria, and Dextranium Bacteria all samples Industries were highest than the critical limit. While the total Moulds and Bacteria Production H2S all samples Industries were less than the critical limit except Kenana and Guneid respectively. Concerning the Total Count of Leuconstoc Mesenteroides Bacteria in sugar, the results revealed all samples Industries were higher than the recommended limit. And the samples Industries were online with the recommended limit concerning the dextran concentration except Guneid industry was highest than the critical limit (75 ppm). The study recommended that the Sudanese Sugar Industry needs to establish proper quality assurance laboratories to help in monitoring the quality and safety of raw materials and end products.In conclusion, the grain yield of maize increased with increasing N rate and plant density up to the optimum. Therefore, it's possible to recommend using a high N rate with both low and medium plant density (< 45,000 plants ha-1) and (45,000 to 65,000plants ha-1) to harvest high grain yield.